ANALYSIS OF THE PROFESSIONALISM OF THE CORRECTIONAL OBSERVATION TEAM IN THE IMPOSITION OF DISCIPLINARY PUNISHMENTS ON INMATES AT RUTAN KELAS IIB KOTA AGUNG - Firdaus, Abhirama; Simanjuntak, Meitisa Vanya (Universitas Nusa Cendana, 2025)
The role of the Correctional Observer Team (TPP) is very important in providing advice and recommendations related to rehabilitation programs, guidance, and security disturbance prevention to the head of the Technical Implementation Unit, where they are required to deliver measurable and professional recommendations encompassing capabilities, quality, facilities and infrastructure, human resources, information technology, and reliability, while employing qualitative methods through the collection of primary and secondary data via observation, interviews, and document studies. The research findings indicate that TPP officers at the Class IIB Detention Center in Kota Agung exhibit a high level of professionalism, reflected in the recommendations made regarding disciplinary actions. Although they adhere to existing standards and consider the six dimensions of professionalism, there are challenges such as limited hearing rooms for disciplinary processes and a lack of components within the Correctional Observer Team Keywords: Professionalism; Correctional Observation Team; Disciplinary Punishment